Effects of monsoon on water quality and trophic state of Kuantan River, Kuantan, Malaysia - Izuddin, Mohd Haikal; Rahman, Mohammad Mustafizur; Yunus, Kamaruzzaman (2017)
North East monsoon brings most rainfall to East Coast state of Malaysia. The high washout due to heavy rainfall during monsoon affects water quality of the Kuantan river. A twelve-months study (April 2014 - March 2015) was conducted in the Kuantan river to elucidate the effects of monsoon on water quality and trophic state of Kuantan River. Turbidity, conductivity, total solid, total suspended solid, salinity, total alkalinity, pH, dissolved oxygen, nutrients like nitrate, nitrite and phosphate of water were studied monthly at two sampling zone located 5 and 10 km up-stream from the Kuantan river estuary. Each sampling zone had three sampling sites. Results indicated that temperature, salinity, dissolve oxygen, conductivity, total alkalinity, nitrate ammonia, chlorophyll A, total suspended solid, and silica varied significantly between zones showing higher silica, chlorophyll A and total suspended solid at the upstream zone compare to downstream zone. Monsoon increased nitrate, silica, and chlorophyll A and decreased temperature, conductivity, TSS, inorganic nitrogen, and total alkalinity. The TRIX values indicated that the Kuantan river was ultra-oligotrophic (very low productive) showing no significant spatial difference. TRIX value increased during pre-monsoon season and monsoon season compare to other sampling months. The results of this study is useful for regular ecological monitoring of the river.